2016
DOI: 10.1007/s00384-016-2667-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter registration study of colorectal cancer: significant variations in radicality and oncosurgical quality—Swiss Group for Clinical Cancer Research Protocol SAKK 40/00

Abstract: In colorectal cancer, surgery considerable variations between different centers were found with regard to radicality and oncosurgical quality, suggesting a potential for targeted improvement of surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We stated that patients with more LNs had a higher risk of LNM. In some surgical and pathological investigations, the LNs yielding or sampling indicated that the number of LNs in colorectal patients have drawn awareness . The previous study confirmed that in colorectal patients with only one metastatic LN, the 5‐year survival rate was significantly higher than those with greater than or equal to two LNs (67% to 39.6%) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We stated that patients with more LNs had a higher risk of LNM. In some surgical and pathological investigations, the LNs yielding or sampling indicated that the number of LNs in colorectal patients have drawn awareness . The previous study confirmed that in colorectal patients with only one metastatic LN, the 5‐year survival rate was significantly higher than those with greater than or equal to two LNs (67% to 39.6%) .…”
Section: Discussionmentioning
confidence: 88%
“…Morphological features and size of LNs were considered as possible manners to determine LNM. The number of LNs is valued in surgery and pathology, yet little attention has been paid to it on the MRI. Contrast‐enhanced MRI is not a mandatory choice to assess rectal cancer in staging; nevertheless, many approaches are trying to reveal its potential importance …”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic perforation of the tumor during surgery is a significant factor because it conditions an increase in local recurrence (Maurer et al, 2017). This fact is independent of the stage and the degree of tumor fixation (Tokodai et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Four RCTs 19,23,27,30 have provided data on this variable and it favors ORR (91%) compared to LARR (84.6%) (p=0.05) with no heterogeneity (I 2 = 0.00 %) (Fig 7). However, none of these recurrence and overall survival [52][53][54] . The rectal perforation rate however, seems to be higher in Fleshman's RCT 30 especially for LARR which is 15.4% compared to 9% for ORR.…”
Section: Perforated Rectummentioning
confidence: 99%